2006
DOI: 10.1051/animres:2006006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preconditioning and extrusion of linseed on the ruminal biohydrogenation of fatty acids. 1. In vivo studies

Abstract: -The extent and intermediates of ruminal biohydrogenation (BH) of fatty acids (FA) from a blend of linseed and wheat bran (70:30) were investigated in the rumen fluid, rumen particle phase and duodenal flow. The blend was ground through a 3 mm screen and used raw or extruded, or was ground through a 6 mm screen and preconditioned. Three dry Holstein cows fitted with ruminal and duodenal cannulas were used in a 3 × 3 Latin square design, with 18 days adaptation. The diet contained 20% (DM basis) of the linseed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Nevertheless, in the study of Privé et al (2010), increasing duration and temperature of oil heating increased trans-10 isomers and decreased trans-11 isomers, contrary to in vivo or in situ observations with roasted or extruded oilseeds (Gonthier et al, 2005;Akraim et al, 2006;TroegelerMeynadier et al, 2006b).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, in the study of Privé et al (2010), increasing duration and temperature of oil heating increased trans-10 isomers and decreased trans-11 isomers, contrary to in vivo or in situ observations with roasted or extruded oilseeds (Gonthier et al, 2005;Akraim et al, 2006;TroegelerMeynadier et al, 2006b).…”
Section: Introductionmentioning
confidence: 79%
“…In the dairy cow diet, fat is usually carried out by oilseeds, which are often heated; for example, by roasting or extrusion. These processes have been shown to have variable effects on BH among studies, which need to be specified and Effects of the heating process of soybean oil and seeds on fatty acid biohydrogenation in vitro explained: heated oilseeds often induced a decrease in cis-9,cis-12 C18:2 and cis-9,cis-12,cis-15 C18:3 BH in vivo (Gonthier et al, 2005), in situ (Chouinard et al, 1997b;Troegeler-Meynadier et al, 2006b), and in vitro (Reddy et al, 1994); however, this partial protection of PUFA against BH was not always noticed (Akraim et al, 2006;Neves et al, 2007;Abdi et al, 2013). Moreover, in most of these studies, heat treatments resulted in an accumulation of BH intermediates, particularly cis-9,trans-11 CLA or trans-11 C18:1, or both.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no differences in milk fat content were reported by Gomez-Cortés et al (2009) when ewes were fed extruded linseed (12% DM). Usually, the dietary lipids in ruminant rations contributed significantly to the energy density of the diet, which is reflected in an increased milk yield (Akraim et al, 2006). The supplementation of TEL affected some of the physical characteristics of milk, and despite the increase in milk pH, this value is within the physiological range reported for sheep milk (Park et al, 2007).…”
Section: Resultsmentioning
confidence: 76%
“…In vivo studies have shown BH extents over 80% for both PUFA [3,10,19], which suggests an underestimation of BH extent with the former investigation methods. The slow in vitro FA disappearance could be due to the accumulation of intermediates and end-products of fermentation or BH in the flasks during incubation.…”
Section: Extent Of Biohydrogenation Of Pufamentioning
confidence: 95%
“…One part of FA methyl esters of each sample was fractionated by argentation TLC (plates 20 × 20 cm, Silica gel 60, Merk KGaA, Germany) as described by Le Doux et al [17], Total and trans-C18:1 FA were analysed by GLC (Agilent 6890N, equipped with a model 7683 auto injector, Network GC System, Palo alto, California, USA) as previously described [3].…”
Section: Analytical Proceduresmentioning
confidence: 99%